More than a carpenter - McDowell, Josh.; McDowell, Sean. (Carol Stream, Ill. : Living Books : Tyndale House Publishers, Inc., 2009)
The author presents the evidence and arguments that convinced him to accept Jesus Christ as his savior.
My story -- What makes Jesus so different? -- Lord, liar, or lunatic? -- What about science? -- The challenge of the new atheism -- Are the Bible records reliable? -- Who would die for a lie? -- What good is a dead Messiah? -- Did you hear what happened to Saul? -- Can you keep a good man down? -- Will the real Messiah please stand up? -- Isn't there some other way? -- He changed my life.
Includes bibliographical references (p. 169-178).
Keywords: Jesus Christ -- Person and offices